Sarcopenia as a Prognostic Factor of Hepatotoxicity and Lower Survival Rate in Chemotherapy of Pancreatic Cancer - A. A. Klunichenko; A. P. Seryakov; A. A. Seryakova; S. M. Demidov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. Evaluation of sarcopenia’s effect on hepatotoxicity in patients with locally advanced and metastatic pancreatic cancer (PC).Materials and methods. A retro-prospective study included 66 patients (30 men and 36 women) with locally advanced and metastatic PC receiving chemotherapy treatment in the form of gemcitabine monotherapy and in combination with platinum, taxanes, fluoropyrimidines in standard chemotherapy protocols. Sarcopenia was observed using computer tomography with intravenous bolus contrast and nonionic contrast medium with iodine concentration 350 mg/ml. Muscle tissue area (cm2) was estimated with two consecutive axial slices at the level of L3 lumbar vertebra. Sarcopenia was determined with the L3 skeletal muscle index (L3SMI) calculated as a ratio of skeletal muscle area at the L3 vertebra to patient’s height squared. Condition was marked as sarcopenia at L3SMI values of 52.4 cm2/m2 in men and 38.5 cm2/m2 in women.Results. Hepatotoxicity was revealed in 57.5% (n = 38) of PC patients receiving chemotherapy, with 60.87% (n = 28) of them having sarcopenia. In patients with sarcopenia and no toxic effects, the total survival median was 41 months, whilst hepatotoxicity combined with sarcopenia was associated with almost a 3 times lower median survival (14.1 months). A better survival trend was observed in a polychemotherapy cohort without sarcopenia, with the total survival median of 17.0 months compared to 15.2 months in such patients with sarcopenia (p = 0.781). A positive trend towards survival was observed in a hepatotoxicity-negative cohort, with the total survival median of 18.7 months compared to 16.9 months in PC patients with toxic side effects (p = 0.174).Conclusions. Sarcopenia may be used as a prognostic factor of lower survival rate and higher hepatotoxic effect of chemotherapy in patients with locally advanced and metastatic pancreatic cancer.